Faktor Internal Dan Faktor Eksternal Yang Mempengaruhi Profitabilitas Bank Umum Syariah - Dayanti, Riski; Indrarini, Rachma (Universitas Negeri Surabaya, 2019)
This research aims to determine the internal and external factors that can affect the value of profitability in Islamic commercial banks in Indonesia. The internal factors consist of CAR, FDR, NPF, and BOPO while the external factors consist of Inflation Rate, Interest Rate, and GDP. This research was conducted using an associative quantitative approach.The sample used in this research amounted to 13 Islamic public banks in the period 2013-2017 using purposive sampling technique. This study uses multiple regression analysis with SPSS version 22.The results of this research indicate that all independent variables used have an effect on profitability. Partially, the NPF, BOPO, and Inflation Rate variables have a significant negative effect on ROA while the CAR, FDR, Interest Rate and GDP variables have no significant effect on ROA.